2015
DOI: 10.5455/ijmsph.2015.21012015220
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining family support and quality of life of elderly population

Abstract: Elderly people have spent a lot of time in the world and have experienced things that future generations will never witness and certainly will not understand. They have taught us respect, manners, traditions, appreciation of things, and how to accept and deal with life experiences. [1] According to an estimate, India will be having the highest aged population in the world by 2025. [2] The quality of life (QOL) of the elderly people has become relevant with the demographic shift toward an aging society. There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 8 publications
6
32
0
7
Order By: Relevance
“…Similar to these findings, Kaur H et al (2015, Uttarakhand), Dasgupta A et al (2018, West Bengal), and Kritika et al (2017, Uttarakhand) also observed significant association between QOL and financial dependency. [16,20,22] 9.1% participants who were having any health problem had poor QOL as compared to 5.6% participants having no health problems (p < 0.05). Quality of life is associated statistically significant with financial dependency and health problems of study participants (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to these findings, Kaur H et al (2015, Uttarakhand), Dasgupta A et al (2018, West Bengal), and Kritika et al (2017, Uttarakhand) also observed significant association between QOL and financial dependency. [16,20,22] 9.1% participants who were having any health problem had poor QOL as compared to 5.6% participants having no health problems (p < 0.05). Quality of life is associated statistically significant with financial dependency and health problems of study participants (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…[17] in their studies also showed statistically significant association between QOL and education. [16,17,20,21,22] This can be explained by the fact that they have a better access to information and health care system which adds to their QOL. 65.5% elderly were living with partner, and among them 48.7% had average QOL followed by 41.1% having good quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acredita-se que o resultado da boa funcionalidade familiar constatado na presente pesquisa possa ser atribuído às boas condições de saúde dos participantes, pois a maioria são independentes nas ABVDs, não foram hospitalizados e nem sofreram quedas no último ano. Estudo sobre os fatores que determinam o apoio familiar e a qualidade de vida de idosos na Índia demonstra que as condições de saúde desta população exercem um papel importante nas relações familiares 23 .…”
Section: Discussionunclassified
“…Menurut hasil penelitian Kaur Harkirat dkk (2015). Dukungan keluarga dengan kualitas hidup lansia dengan nilai p-value =0,003 artinya ada hubungan antara dukungan keluarga dengan kualitas hidup lansia (Kaur, 2015).…”
Section: Metodeunclassified